Laki-Laki yang Berhubungan Seksual dengan Laki-Laki (LSL) pada Penderita HIV dan Sifilis Sekunder: Laporan Kasus - Ida Ayu Cintya Pradnyandari; Anak Agung Candra Wahyuni; Putu Dyah Ayu Saraswati (PT Kalbe Farma Tbk., 2024)
The incidence of sexually transmitted infections in man who have sex with man (MSM) is increased among human immunodeficiency virus (HIV) patients. HIV and syphilis are two sexually transmitted diseases that frequently interact and modify the symptoms and signs of the disease. A case of a 27-year-old male with generalized multiple erythematous plaques including palms and soles since 4 days ago was reported. The patient has been diagnosed with HIV since 2017. The patient is sexually active with a male sex partner and rarely uses condoms. Diagnosis of syphilis is made based on anamnesis, physical examination, and laboratory tests. The treatment was benzathine penicillin G 2.4 million units in 3 doses. The combination of HIV and syphilis needs longer therapy and requires serological follow-up for up to 24 months.